Gato hyalinus gen. et sp. nov., an unusual araphid tube-dwelling diatom from Western Pacific and Caribbean islands - Lobban, Christopher S.; Navarro, J. Nelson (Phytotaxa, 2013)
A new species of tube-dwelling diatom, unusual in being araphid, is described from benthic coral reef habitats in Guam, Palau, Puerto Rico and Jamaica. Gato gen. nov. is heteropolar and heterovalvar, exhibits very fine striae delimiting a narrow and irregular sternum, and possesses a series of rimmed pores on each side of the foot pole. One valve of the frustule has a rimoportula at the foot pole, but both valves possess a rimoportula at the head pole. The generitype, G. hyalinus sp. nov. forms small, branched colonies. Individual cells are oval, slightly tapered along the apical axis, 30–40 µm x 13–15 µm, with 60–70 striae in 10 µm. On the foot pole with a rimoportula the rimmed pores are connected to the sternum by diagonal striae; several additional rimmed pores interrupt transapical striae further up both valves. We compare valve structure of G. hyalinus with Florella portoricensis and F. pascuensis, which we report for the first time from the Marshall Islands, and to Licmophora spp. We find no taxa to which this genus is related, and can identify no structure potentially homologous to the series of rimmed pores among the diatoms.